ANALISIS POTENSI ENERGI BARU TERBARUKAN SEBAGAI ENERGI ALTERNATIF PENGGANTI ENERGI FOSIL DI WILAYAH PROBOLINGGO TIMUR - Agus Sudibyo; Agung Nugroho; Burhan Fazzry (Indie Press, 2025)
New renewable energy comes from natural resources that can be replenished. It has a smaller environmental impact than fossil energy. EBT includes various types of energy, such as solar, wind, water, geothermal, and biomass energy. EBT's role can gradually increase from year to year, contributing up to 5%. To achieve this, breakthrough efforts are necessary to gradually and systematically develop alternative energy sources. In line with increasing energy demands, national energy policy encourages EBT to play a greater role in the future by exploring its considerable potential in local areas. This will ensure that areas in need of energy from EBT sources no longer rely on fossil energy. To this end, it is necessary to map the utilization of the potential of new renewable energy in the area, especially in the eastern region of Probolinggo Regency, as the object of research. This research explores the development of EBT, including bioenergy, such as biogas and biomass. Mapping the utilization of new renewable energy potential in the eastern region of Probolinggo Regency is expected to provide a foundation for policy development in the context of EBT potential as an alternative energy source.